Sport, Class and Identity at Swansea, 1870–1914. (1st December 2019) - Rees, Barry
This article discusses the growth of rugby as the most popular pastime in Swansea for most of the period 1870–1914. It examines how the game shaped an inclusive civic identity from the 1890s and how this was layered alongside other identities. It also examines how social class and gender were negotiated during the game's rise. Swansea's middle class stamped its authority on local government and voluntary institutions and the town's rugby club was among the foremost of these institutions by the end of the 1870s. It is argued that sport offered a unique opportunity for new civic alliances.